Angiostatic activity of obtustatin as α1β1 integrin inhibitor in experimental melanoma growth - Brown, Meghan C. (2008)
The presented results show the effect of targeting of collagen receptor, α1β1 integrin expressed on the endothelial cells on the development of experimental melanoma and pathological angiogenesis. Obtustatin, a snake venom KTS-disintegrin, was applied as a specific inhibitor of this integrin. This low molecular weight peptide revealed a potent therapeutic effect on melanoma progression in two animal systems, mouse and quail. Its oncostatic effect was related to the inhibition of angiogenesis. Obtustatin inhibited the neovascularization ratio on the CAM embryo of quail, which was pathologically induced by the developing tumor. The i.v. administration of obtustatin completely blocked cancer growth of MV3 human melanoma in nude mice. In B16F10 syngeneic mouse model treatment with the disintegrin revealed a lower effect, although the development of the tumor was significantly reduced for both dosages. The mechanism of obtustatin action is related to the blocking of microvascular endothelial cell proliferation, which undergoes apoptosis in caspase-dependent manner. Summarizing, we present studies of low molecular weight disintegrin, obtustatin as a potential therapeutic compound for treatment of melanoma that contain a high level of vascularization.